Herpes zoster ophthalmicus following recombinant zoster vaccine: A case report and brief literature review - Joshua M. Garcia; Ramez I. Haddadin (IDCases, 2024)
Purpose: Immunizations have long been pivotal in preventing diseases like HZ (herpes zoster), caused by VZV (varicella zoster virus). This study aims to evaluate the efficacy and safety of the RZV (recombinant zoster vaccine) compared to the ZVL (zoster vaccine live) and to report rare adverse events following RZV administration. Observation: Herein, we report an unusual case of a 59-year-old man who developed a V1-limited rash with a positive HZ PCR (polymerase chain reaction) test following administration of RZV in the United States. Conclusion: The development of RZV has significantly improved the prevention of HZ compared to ZVL. Nevertheless, rare adverse events, such as dermatomal reactions, underscore the importance of ongoing monitoring and research into the immunomodulatory effects of RZV. Physicians should continue to administer the RZV to patients but be cognizant that reactivation may rarely subsequently occur. Case Presentation: The patient with a history of benign prostatic hyperplasia was treated at an outside hospital two days after receiving the RZV complaining of paresthesia and a rash on his nasolacrimal area and forehead. The patient presented to the ED (emergency department), 9 days post-vaccination due to persistence of his symptoms despite use of amoxicillin, valacyclovir, and an unidentified eye drop. The dose of valacyclovir was increased, and he completed 1 g TID (three times a day) PO (per orally) for 10 days with subsequent resolution of symptoms. A positive PCR test confirmed the diagnosis of HZ. Topical mupirocin ointment was initiated and the patient was referred for ophthalmologic evaluation.